2022
DOI: 10.1039/d2cy00688j
|View full text |Cite
|
Sign up to set email alerts
|

Size effect of Ru particles on the self-reforming-driven hydrogenolysis of a lignin model compound

Abstract: Particle size always has a great influence on catalytic performance. In this work, we investigated the size effect of Ru colloids on the self-reforming-driven hydrogenolysis of lignin model compound by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Wang et al executed a study that amalgamated various steps such as dehydrogenation of aliphatic hydroxyl groups, hydrogenolysis of ether and methoxyl bonds, and hydrogen generation via methanol autothermal reforming, with Pt/NiAl 2 O 4 serving as the catalyst. [184] This holistic strategy led to the high-selectivity production of 4-alkylphenol. Furthermore, the self-reformingdriven methodology proved to be adaptable, as evidenced by its application to the conversion of natural depolymerized lignin oils and birch lignin.…”
Section: Lignin As Substratementioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al executed a study that amalgamated various steps such as dehydrogenation of aliphatic hydroxyl groups, hydrogenolysis of ether and methoxyl bonds, and hydrogen generation via methanol autothermal reforming, with Pt/NiAl 2 O 4 serving as the catalyst. [184] This holistic strategy led to the high-selectivity production of 4-alkylphenol. Furthermore, the self-reformingdriven methodology proved to be adaptable, as evidenced by its application to the conversion of natural depolymerized lignin oils and birch lignin.…”
Section: Lignin As Substratementioning
confidence: 99%
“…Wang et al. executed a study that amalgamated various steps such as dehydrogenation of aliphatic hydroxyl groups, hydrogenolysis of ether and methoxyl bonds, and hydrogen generation via methanol autothermal reforming, with Pt/NiAl 2 O 4 serving as the catalyst [184] . This holistic strategy led to the high‐selectivity production of 4‐alkylphenol.…”
Section: Hydrogen Transfer Lignin Refinerymentioning
confidence: 99%
“…Wang's group used NiAl 2 O 4 loading with various noble metals to produce alkylphenol from lignin by self-reforming-driven depolymerization and hydrogenolysis, and found that demethoxylation is the rate-determining step in the whole process. [17][18][19] Rong and Li reported the highly selective conversion of guaiacol to phenol in pure water by a versatile nano-porous Ni catalyst, and the mechanism showed that the initial hydrogen source came from water splitting on the surface of the Ni catalyst, and the subsequent aqueous phase reforming of methanol generated more hydrogen and further accelerated the hydrodeoxygenation process. 20 Our group proposed self-supported hydrogenolysis (SSH) of aromatic ethers to produce arenes using the methoxy group as the hydrogen source over RuW/SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…22 These articles used water as the reaction medium, which is a cheap, non-toxic and environmentally friendly reaction medium. [15][16][17][18][19][20][21][22] The reported works on the STH process are based on precious metal catalysts. However, the resources of precious metals are very limited, and mining and purification release large amounts of CO 2 compared with non-precious metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation